2017
DOI: 10.1186/s12911-016-0398-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulated case management of home telemonitoring to assess the impact of different alert algorithms on work-load and clinical decisions

Abstract: BackgroundHome telemonitoring (HTM) of chronic heart failure (HF) promises to improve care by timely indications when a patient’s condition is worsening. Simple rules of sudden weight change have been demonstrated to generate many alerts with poor sensitivity. Trend alert algorithms and bio-impedance (a more sensitive marker of fluid change), should produce fewer false alerts and reduce workload. However, comparisons between such approaches on the decisions made and the time spent reviewing alerts has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…30 Several research groups reported that simple rules of sudden bodyweight change in patients with heart failure were demonstrated to generate many alerts with poor sensitivity. 6,[30][31][32] Different methods are being used to interpret values outside thresholds in telemonitoring chronic heart failure. Some telemonitoring programmes depend only on knowledge of the healthcare professional interpreting the data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Several research groups reported that simple rules of sudden bodyweight change in patients with heart failure were demonstrated to generate many alerts with poor sensitivity. 6,[30][31][32] Different methods are being used to interpret values outside thresholds in telemonitoring chronic heart failure. Some telemonitoring programmes depend only on knowledge of the healthcare professional interpreting the data.…”
Section: Discussionmentioning
confidence: 99%
“…It stands to reason that when set too wide, then there is a high risk that the patient is decompensated before an alert trigger is generated whereas thresholds which are set too tightly could lead to many 'false' alert triggers. 6 The aim of this systematic review was, first, to assess how algorithms in non-invasive telemonitoring programmes were reported and, secondly, which subsequent thresholds for biometric parameters (bodyweight, blood pressure, heart rate) and symptom questions were used to monitor symptoms of heart failure and/or guide titration of heart failure medication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, comparisons between various studies are difficult and, as a result, many issues remain unresolved. Improved detection of deterioration could help telemonitoring nurses to more effectively direct their attention to patients at higher risk and provide better care through telemonitoring if properly integrated [16]. This study aimed to determine if there was any additional value of including trends in blood pressure (BP) and heart rate (HR), which are often captured in conjunction with weight, into the detection of deterioration.…”
Section: Introductionmentioning
confidence: 99%
“…The use of telemonitoring devices and systems can provide a safe and effective monitoring of these patients. The measurement of physical and biological parameters essential for the analysis of the evolution and treatment of the disease prescribed by the health professionals, allows them to evaluate the data and take decisions to change or maintain prescriptions or health care for the monitored patient [4], [7].…”
Section: Introductionmentioning
confidence: 99%